The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0050446
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Functions of Natural Killer Cells in Critically-Ill Septic Patients

Abstract: RationaleNatural killer cells, as a major source of interferon-γ, contribute to the amplification of the inflammatory response as well as to mortality during severe sepsis in animal models.ObjectiveWe studied the phenotype and functions of circulating NK cells in critically-ill septic patients.MethodsBlood samples were taken <48 hours after admission from 42 ICU patients with severe sepsis (n = 15) or septic shock (n = 14) (Sepsis group), non-septic SIRS (n = 13) (SIRS group), as well as 21 healthy controls. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 47 publications
(64 reference statements)
10
59
0
3
Order By: Relevance
“…NK cells are a major source of interferon-g (IFN-g), a potent inflammatory cytokine, and early depletion of NK cells improved survival in sepsis models in the mouse. 36,37 We also recently observed that both NK-cell cytotoxicity and IFN-g production were decreased in sepsis, 38 consistent with similar results obtained in mice. 39 Considering the sequence of opposite events that are at work during sepsis, NK cells might have a dual role in sepsis, first contributing to the amplification of the inflammatory response during the early steps of SIRS and then, impaired during CARS and thus participating to its detrimental consequences.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…NK cells are a major source of interferon-g (IFN-g), a potent inflammatory cytokine, and early depletion of NK cells improved survival in sepsis models in the mouse. 36,37 We also recently observed that both NK-cell cytotoxicity and IFN-g production were decreased in sepsis, 38 consistent with similar results obtained in mice. 39 Considering the sequence of opposite events that are at work during sepsis, NK cells might have a dual role in sepsis, first contributing to the amplification of the inflammatory response during the early steps of SIRS and then, impaired during CARS and thus participating to its detrimental consequences.…”
Section: Discussionsupporting
confidence: 88%
“…39 Considering the sequence of opposite events that are at work during sepsis, NK cells might have a dual role in sepsis, first contributing to the amplification of the inflammatory response during the early steps of SIRS and then, impaired during CARS and thus participating to its detrimental consequences. 38,40,41 Our data on B7-H6 expression during inflammation provide a novel perspective on the link between microbial infection and NK-cell activation. First, B7-H6 was selectively induced on the surface of CD14…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have revealed an early decrease of NK-cell function in patients with septic or severe TBI [15,16] .…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have demonstrated considerable role for NKG2D in protective function against virus infected or transformed cells [5,37,45]. The liver lymphocyte population is enriched with NK cells and these cells are one of the main cell populations, expressing NKG2D [11,42]. The major NK cell functions include direct killing of target cells as well as cytokine production such as IFN-c [11].…”
Section: Nkg2d Polymorphism Effects On Peginterferon Alfa-2a/ribavirimentioning
confidence: 99%
“…The liver lymphocyte population is enriched with NK cells and these cells are one of the main cell populations, expressing NKG2D [11,42]. The major NK cell functions include direct killing of target cells as well as cytokine production such as IFN-c [11]. NKG2D ligation induces calcium flux, cytokine release, and cytotoxicity in NK cells.…”
Section: Nkg2d Polymorphism Effects On Peginterferon Alfa-2a/ribavirimentioning
confidence: 99%